The Effect of Spirulina Plant Suspension on the Productivity of Livestock and Poultry and the Quality of Their Products - DSc Salimova I. Y.; PhD Salimova N.Y. (American Journal of Biodiversity, 2026)
The increasing global demand for sustainable and biologically active feed additives has intensified scientific interest in microalgae-based supplements within modern animal production systems. Among these, Spirulina platensis, a protein-rich cyanobacterium containing 60–70% high-quality protein, essential amino acids, polyunsaturated fatty acids, vitamins, minerals, carotenoids, and other antioxidant compounds, is considered a promising natural alternative to synthetic growth promoters. This article provides a comprehensive analysis, based on contemporary scientific literature and experimental evidence, of the effects of a Spirulina platensis-based plant suspension on the productivity of livestock, poultry, and fish, as well as on the qualitative indicators of animal-derived products. Particular attention is given to the strategic role of cattle breeding, poultry farming, and aquaculture in ensuring national food security and improving the nutritional value of food products. The biological efficacy of active feed additives is examined, with emphasis on their immunomodulatory, antioxidant, metabolic-enhancing, and growth-promoting properties. Experimental trials conducted under controlled feeding conditions involved the supplementation of animal diets with defined concentrations of Spirulina suspension over a specified production period. Key productivity parameters—including average daily gain, feed conversion ratio, live body weight, reproductive performance, and health-related biochemical markers—were evaluated. In poultry, egg production rate, egg mass, shell thickness, and yolk pigmentation were assessed, while in livestock and aquaculture species, milk yield, milk composition, meat quality characteristics, and fish growth performance were analyzed.